2006
DOI: 10.1002/uog.2716
|View full text |Cite
|
Sign up to set email alerts
|

Isolated ventricular septal defects detected by color Doppler imaging: evolution during fetal and first year of postnatal life

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
63
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 17 publications
(33 reference statements)
8
63
3
4
Order By: Relevance
“…Age at first echocardiographic examination and the length of the follow-up period may influence the spontaneous closure rate (9,10). It has been demonstrated that 12.5-31% of m-VSDs can undergo spontaneous closure during fetal life (11,12). Results may vary due to the different classifications of VSDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age at first echocardiographic examination and the length of the follow-up period may influence the spontaneous closure rate (9,10). It has been demonstrated that 12.5-31% of m-VSDs can undergo spontaneous closure during fetal life (11,12). Results may vary due to the different classifications of VSDs.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of chromosomal anomalies associated with fetal isolated m-VSDs is controversial. Two large series reported a rate of 28.6-38.2% chromosomal anomalies associated with m-VSDs but included cases with extracardiac anomalies and associated known chromosomal anomalies (12,13). Another study determined a 6.2% prevalence of aneuploidy associated with isolated VSD, but the study included a limited number of cases (11).…”
Section: Discussionmentioning
confidence: 99%
“…6 Color Doppler sonography allows confirmation of the existence of VSDs by showing the presence of blood shunts between ventricles, and at present this approach is considered the method of choice for diagnosing this condition. 5,6 However, there are more difficulties in applying this technique to fetuses than to neonates. In neonates, the pressure gradient existing between the left and right ventricles produces a high-velocity jet that can be easily identified on color Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 On the other hand, during intrauterine life there is no pressure gradient between the left and right ventricles because of the physiologic patency of the ductus arteriosus and the foramen ovale; therefore, a more subtle low-velocity bidirectional shunt is present. 4,5 Detection of shunting is possible albeit dependent on a good color-operating setting and proper interrogation of the septum at an angle perpendicular to the defect. A further difficulty in diagnosing VSDs in the fetus arises from the fact that the septum does not lie on the same plane, and systematic visualization of all parts of the interventricular septum is necessary to exclude the presence of a defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation